2019
DOI: 10.1101/509919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The respiratory virome and exacerbations in patients with chronic obstructive pulmonary disease

Abstract: Introduction: Exacerbations are major contributors to morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD), and respiratory bacterial and viral infections are an important trigger for the occurrence of such exacerbations. However, using conventional diagnostic techniques, a causative agent is not always found. Metagenomic next-generation sequencing (mNGS) allows analysis of the complete virome, but has not yet been applied in COPD exacerbations. Objectives: To study the respir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…Results presented in pharyngeal clinical samples showed that the greatest amounts of viral sequences from mammalian viruses were present in the families Coronaviridae , Anelloviridae , and Paramyxoviridae , Coronaviridae and Anelloviridae comprising the major part of the composition. Both Coronaviridae and Anelloviridae were detected in the same sample in the present research ( Figure 4B ), which was inconsistent with previous studies where Anelloviridae were not detected in the Coronaviridae -positive samples and Coronaviridae were not detected in the Anelloviridae -positive samples ( van Rijn et al, 2019 ). We also observed that the M3 did not detecte Herpesviridae , which were thought to have possibly integrated into the human genome.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Results presented in pharyngeal clinical samples showed that the greatest amounts of viral sequences from mammalian viruses were present in the families Coronaviridae , Anelloviridae , and Paramyxoviridae , Coronaviridae and Anelloviridae comprising the major part of the composition. Both Coronaviridae and Anelloviridae were detected in the same sample in the present research ( Figure 4B ), which was inconsistent with previous studies where Anelloviridae were not detected in the Coronaviridae -positive samples and Coronaviridae were not detected in the Anelloviridae -positive samples ( van Rijn et al, 2019 ). We also observed that the M3 did not detecte Herpesviridae , which were thought to have possibly integrated into the human genome.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results for M3 proved to be robust for viral verification but also to be accurate for viral genome analysis and evolutionary study. We further verified OC43 viruses in three original samples using RT-PCR with pan-coronavirus primers ( Woo et al, 2005 ), indicating that it might have been one of the causes of acute COPD exacerbation ( Wylie, 2017 ; van Rijn et al, 2019 ). Furthermore, the other nine Anelloviridae family viruses were also characterized ( Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Library preparation and sequencing were performed using a previously validated protocol [ 15 , 16 ]. Briefly, 200 μl of patient samples were spiked with equine arteritis virus (EAV) and phocid herpesvirus-1 (PhHV-1) prior to NA extraction using the Magnapure 96 DNA and Viral NA Small volume extraction kit on the MagnaPure 96 system (Roche, Basel, Switzerland) resulting in 100 μL nucleic acid-containing eluate.…”
Section: Methodsmentioning
confidence: 99%